2019
DOI: 10.1007/s11908-019-0679-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Enterobacteriaceae in Solid Organ Transplantation: Management Principles

Abstract: Purpose of Review Carbapenem-resistant Enterobacteriaceae (CRE) have emerged as a worldwide problem. Given their degree of immunosuppression and the level of contact with the healthcare system, solid organ transplant (SOT) recipients are at a disproportionately higher risk of acquisition, colonization, and infection with CRE, and outcomes from infection tend to be worse compared to non-transplant patients. Therapeutic options are limited for CRE infections although several newer agents have recently been appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 131 publications
(152 reference statements)
0
6
0
Order By: Relevance
“…Over the past few years, carbapenem-resistant Enterobacteriaceae (CRE), the most frequent pathogens responsible for nosocomial infections, have emerged and rapidly spread all over the world, posing great challenges to human health [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Conventionally, carbapenem antibiotics have been considered the most effective among available antibacterial agents for the treatment of infections caused by Enterobacteriaceae (e.g., E. coli and Klebsiella pneumoniae ), and are still being used as the antibiotics of last-resort to date [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, carbapenem-resistant Enterobacteriaceae (CRE), the most frequent pathogens responsible for nosocomial infections, have emerged and rapidly spread all over the world, posing great challenges to human health [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Conventionally, carbapenem antibiotics have been considered the most effective among available antibacterial agents for the treatment of infections caused by Enterobacteriaceae (e.g., E. coli and Klebsiella pneumoniae ), and are still being used as the antibiotics of last-resort to date [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Novel β-lactamase inhibitors, such as vaborbactam, avibactam and relebactam, are capable of counteracting the effect of KPC and ESBLs [128]. Lately, new β-lactam/β-lactamase inhibitor combinations, namely meropenem/vaborbactam, ceftazidime/avibactam and imipenem/cilastatin/relebactam were approved by the US FDA (MD, USA) for the treatment of infections caused by CRE [118,129,130].…”
Section: Molecular Assaymentioning
confidence: 99%
“…[6][7][8] This is likely driven by SOT recipients' multicomorbidity, frequent healthcare and antibiotic exposures, frequent procedures, and chronic indwelling medical devices. [9][10][11][12] Notably, however, several studies have identified transplant status as an independent risk factor for CRE infection, even after adjusting for other risk factors, 7 suggesting there may be issues unique to transplantation that increase the risk for CRE infection. 12 Furthermore, prior studies have indicated that outcomes following CRE infection in SOT recipients are poor, with rates of graft failure and death ranging between 12% and 66%, depending on the transplant cohort, the type of CRE infection studied, and the duration of follow-up.…”
Section: Introductionmentioning
confidence: 99%